2019
DOI: 10.33160/yam.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Ossified Metaplastic Spinal Meningioma Without Psammomatous Calcification: A Case Report

Abstract: Meningiomas constitute approximately 25% of primary spinal cord tumors, and 1% to 5% are calcified. Ossification is a rare event and the etiology of ossification in meningiomas is not well known. We present the case of a 29-year-old female with a rare case of ossified thoracic spinal metaplastic meningioma. The tumor was successfully resected, and pathology confirmed ossified metaplastic meningioma. On histopathological examination, only mature bone tissue and tumor cells were present in the region containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Ossification differs from these is seen in Psammomatous Meningioma. 13 We diagnosed the Meningioma as Grade 1 based on, its microscopic study and its site, in the microscopic study Meningothelial cells and whorl patterned psammoma bodies were observed. Hence, it is a Psammomatous type of Grade 1 Meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Ossification differs from these is seen in Psammomatous Meningioma. 13 We diagnosed the Meningioma as Grade 1 based on, its microscopic study and its site, in the microscopic study Meningothelial cells and whorl patterned psammoma bodies were observed. Hence, it is a Psammomatous type of Grade 1 Meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…However, some reports ( 4 , 8 , 10 , 15 , 21 ) have occasionally found that ossification can occur without psammoma bodies, which may not support the hypothesis. Hence, most studies prefer to believe that ossification is secondary to the metaplasia of arachnoid cells and interstitial cells, which induce the synergistic effect of osteoblast, fibroblast, and angiogenesis components in bone tissue formation ( 4 , 8 , 10 , 23 ). Up to now, seven studies have mentioned the formation of hematopoietic tissue in OSM.…”
Section: Discussionmentioning
confidence: 99%
“…Myxoid metaplastic meningioma are characterized by their excessive hyaluronic acid and chondroitin sulfate [ 5 , 7 , 9 , 12 ]. Osseous subtypes are confirmed by the presence of mature bone tissue and tumor cells in regions containing no psammoma bodies [ 1 , 14 , 15 , 17 , 18 ]. A recent literature review by Choi et al [ 2 ] described 26 metaplastic meningiomas, including 12 osseous subtypes, nine lipomatous subtypes, four xanthomatous subtypes, and one cartilaginous subtype.…”
Section: Discussionmentioning
confidence: 99%